2021
DOI: 10.5811/westjem.2021.2.49626
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Emergency Department Visits at a Canadian Academic Tertiary Care Center

Abstract: Introduction: Public health response to the coronavirus 2019 (COVID-19) pandemic has emphasized social distancing and stay-at-home policies. Reports of decreased emergency department (ED) visits in non-epicenters of the outbreak have raised concerns that patients with non-COVID-19 emergencies are delaying or avoiding seeking care. We evaluated the impact of the pandemic on ED visits at an academic tertiary care center. Methods: We conducted an observational health records review between January 1–April 22, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…7 Several Canadian studies also reported that emergency department visits declined during the first wave of the pandemic, possibly owing to avoidance of in-person urgent care from fear of contracting SARS-CoV-2. [8][9][10] In later stages of the pandemic, questions arose about the quality of virtual care and the broader system effects of reduced access to in-person care, such as patients substituting emergency department visits when in-person care options were unavailable. [11][12][13] The impact of virtual care on emergency department use has been studied elsewhere, but we are not aware of published studies in the context of the COVID-19 pandemic in analysis to estimate the association between the proportion of a physician's visits that were delivered virtually and the number of emergency department visits among their enrolled patients.…”
mentioning
confidence: 99%
“…7 Several Canadian studies also reported that emergency department visits declined during the first wave of the pandemic, possibly owing to avoidance of in-person urgent care from fear of contracting SARS-CoV-2. [8][9][10] In later stages of the pandemic, questions arose about the quality of virtual care and the broader system effects of reduced access to in-person care, such as patients substituting emergency department visits when in-person care options were unavailable. [11][12][13] The impact of virtual care on emergency department use has been studied elsewhere, but we are not aware of published studies in the context of the COVID-19 pandemic in analysis to estimate the association between the proportion of a physician's visits that were delivered virtually and the number of emergency department visits among their enrolled patients.…”
mentioning
confidence: 99%
“…More recently, smartwatches have been used to detect pre-symptomatic COVID infections (Mishra et al, 2020). Common and affordable smartwatches and fitness trackers might support remote patient monitoring (RPM) if the emergent data is high-enough quality to inform safe decision making (Iqbal et al, 2021, Kwok et al, 2021; Lu et al, 2020, Kang & Exworthy, 2022). Remote patient monitoring is particularly important for patients living in remote and rural areas where in-person care can be limited (Fraser et al, 2022; Liao et al, 2019; Canali et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With CT considered the power horse of ED imaging, radiologists’ on-call workload more than doubled the growth rate of ED visits over an 8-year period [ 3 ]. However, the upward trend was abruptly reversed in 2020 following declaration of COVID-19 pandemic and related measures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%